Strategic Leadership and Innovation Adoption: A Cross-Cultural Analysis of SMEs in Italy - Colombo, Beatrice (European Journal of Business and Strategic Management, 2024)
Purpose: The aim of the study was to analyze the strategic leadership and innovation adoption: a cross-cultural analysis of SMEs in Italy. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study suggests that effective strategic leadership significantly influences innovation adoption among SMEs in Italy, highlighting the importance of leadership in fostering a culture of innovation. Furthermore, the cross-cultural analysis underscores the need for culturally sensitive approaches to leadership and innovation strategies, recognizing the unique contexts and challenges faced by SMEs operating in Italy Unique Contribution to Theory, Practice and Policy: Transformational leadership theory, Hofstede's cultural dimensions' theory & Technology acceptance model (TAM) may be used to anchor future studies on analyze the strategic leadership and innovation adoption: a cross-cultural analysis of SMEs in Italy. Practical recommendations should focus on empowering SME leaders in Italy to foster a culture of innovation and embrace digital transformation. Policymakers should design and implement supportive policies that incentivize innovation adoption and create an enabling environment for SMEs in Italy.